Periodismo deportivo y nuevos escenarios del ejercicio profesional - Martínez Fuentes, David Enrique (2024)
The issue related to sports journalism and the new scenarios of professional practice arises because there is a problem in the immediate management of information through the various professionals who look for traditional models and do not generate innovation in digital media, the problem encompasses the referring question: Why is innovation and creativity required in professionals for adequate perception by the user who uses technology to communicate? The main objective is to analyze the main strategies that innovative sports journalism has to capture the attention and perception of the user through new alternatives for the dissemination of quality news. The applied methodology has a qualitative and quantitative approach that is carried out through an exploratory, non-experimental, correlational and descriptive study; The main instruments used to collect information are observation, surveys and interviews. The results achieved will allow decisions to be made about what would be the main strategies that will be used to expand the coverage of the sports program and carry out the necessary management to expand the spectrum of service and communication to the user. In conclusion, the development of creative and innovative strategies will encourage digital media to increase the select audience of Internet users who like sports information.